Quantitative Method for Predicting the Number of New Students in Private Colleges (Case Study on XYZ University) - Ramdan Padmakusumah, Rizal; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
Forecasting the number of new students there is a certain period for private universities is very important to predict the resource requirements of these private universities. Accurate forecasting will increase the effectiveness and efficiency of business in private tertiary institutions. Quantitative forecasting methods are forecasting methods that are commonly used by various organizations, including private tertiary institutions. This study tries to predict the number of new students at private universities in a certain period by using three quantitative methods, namely: the four-monthly moving average method with weighting, the exponential refinement method, and the trend analysis method, and then assess which method is the best (and most accurate) in predicting the number of new students. This research was conducted at one of the best private tertiary institutions in Indonesia, which kept its original identity a secret and was given the identity in this study as XYZ University. The research conducted was a qualitative study using secondary data, namely actual new student data for 5 years (2015 to 2019). The results showed that the exponential refinement method was better used in predicting new student data for a certain period than the moving average method with weighting as well as the trend analysis method. Forecasting results using exponential refinement methods before use, of course, must first consider factors, situations, and other assumptions in the predicted period.